Design, analysis and fabrication of automatic plant watering system - Donny Osmond, Oxana Sumba (2024)
The Automatic Plant Watering System is a crucial innovation in the field of agriculture, aiming to alleviate the challenges associated with manual watering and ensure the optimal growth of plants. In this era of increasing population and limited resources, efficient irrigation systems are necessary to conserve water and enhance crop productivity. The existing conventional methods of plant watering are labour- intensive and prone to human error, leading to inefficient use of water and inadequate hydration for plants. Moreover, the lack of real-time monitoring and control mechanisms often results in under or over-watering, leading to suboptimal growth and reduced yield. Therefore, there is an urgent need to develop an automated system that can accurately monitor soil moisture levels and dispense water accordingly, ensuring the appropriate hydration of plants. The main objective of this final year project is to design and implement an Automatic Plant Watering System that utilizes sensor technology and intelligent control algorithms to maintain the ideal moisture levels in the soil. The system will enable real-time monitoring of soil moisture and automatically activate the irrigation mechanism when required. Additionally, it will incorporate a user-friendly interface for setting custom watering schedules and providing notifications/alerts regarding water levels, ensuring convenient management and minimal human intervention. Expected result upon successful completion of this project, we anticipate the development of a reliable and efficient Automatic Plant Watering System that optimizes water usage, minimizes manual labour, and maximizes plant growth. The system's ability to accurately monitor soil moisture levels and dispense water in a timely manner will result in improved crop yield, reduced water wastage, and enhanced resource sustainability. Furthermore, the user-friendly interface will empower farmers and gardeners with better control and management of their irrigation processes, ultimately contributing to the advancement of smart farming practices and addressing the challenges of modern agriculture.